Telaṅgāṇa pōrāṭa pāṭalu : 1946-51 Telaṅgāṇa raitāṅga sāyudha pōrāṭa pāṭalu - Cārvāka (Viplava Racayitala Saṅghaṃ pracuraṇa, 1972)
Collection of revolutionary lyric poetry of the Telengana region of Andhra Pradesh.